Adaptive system for correcting optical aberrations of high-power lasers with dynamic determination of the reference wavefront. (July 2021) - Kotov, A.V.; Perevalov, S.E.; Starodubtsev, M.V.; Zemskov, R.S.; Alexandrov, A.G.; Galaktionov, I.V.; Kudryashov, A.V.; Samarkin, V.V.; Soloviev, A.A.
Abstract: We present the results of the aberration correction of laser radiation wavefront using a dynamic method for determining the reference wavefront. The method, which is based on the processing of synchronously obtained data on the near- and far-field zones, significantly improves the focusing quality with active wavefront correction, especially under conditions of dynamic aberrations. An increase in the Strehl number S from 0.7 to 0.86 is demonstrated when a beam 18 cm in diameter is focused by an F /2.5 parabolic mirror.